KUALITAS PELAYANAN TIM PELAKSANA SISTEM LAYANAN RUJUKAN TERPADU (SLRT) DINAS SOSIAL PEMBERDAYAAN PEREMPUSN DAN PERLINDUNGAN ANAK DI NAGARI SAGO SALIDO KABUPATEN PESISIR SELATAN - Vrisco Chentari; Karjuni Dt Ma’ani (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2020)
This research is motivated because there are still a large number of poor and vulnerable people in Nagari Sagari Salido, while the government has implemented an Integrated Referral Service System (SLRT) program that provides social assistance to help people get out of the poverty zone, this Integrated Referral Service System (SLRT) is a one-stop service identifies the needs and complaints of the poor and vulnerable then they will be introduced to social protection and coping programs for the poor, make referrals, and help with complaint handling to ensure that these complaints are handled properly